The Influence of Think Pair Share Cooperative Learning Models on Outcome in Integrated Thematic Learning for Grade V Elementery School - Yuri Yuliajati Putri; Reinita Reinita (Edumaspul: Jurnal Pendidikan, 2022)
The goal of this research is to see how the Think Pair Share (TPS) cooperative model affects student learning outcomes in integrated theme learning in class V Cluster I, Jurai District IV. This study used a non-equivalent control group design, which is a type of quasi-experimental methodology. This research covered all pupils in class V Cluster I, Jurai District IV. The experimental and control classes were created through purposeful sampling, with class V A acting as the experimental class and class V B functioning as the control class. The hypothesis was evaluated with a t test at a 95% confidence level (α = 0.05), and the results indicated that tcount > ttable (2,434 > 2,045), showing that H1 is correct. As a consequence, using the Think Pair Share (TPS) cooperative learning technique in integrated theme learning in class V of Elementary School had a significant influence on student learning outcomes.